Statistical year book 1967-68 - Central Bureau of Statistics, Accra; Central bureau of Statistics, Accra (Accra, Ghana : Central bureau of Statistics, 1970)
This statistical year book contains a 1967-1968 statistical detail of the Republic of Ghana.
Includes index.
asm 23/01/2019
Ref.
Keywords: Statistics; Ghana